Understanding neuroticism and social media: A systematic review. (1st January 2021) - Bowden-Green, Thomas; Hinds, Joanne; Joinson, Adam
Abstract: Despite people spending nearly 10% of each day on social media platforms, many also now appear to be anxious to limit the intrusion of social media into their everyday lives. Given the known link between mental anguish and trait neuroticism, understanding how personality relates to social media usage has become an important area of study in recent years. As a result, there is an abundance of articles exploring neuroticism and social media across a variety of contexts. This article synthesizes and reviews the existing work, based on a systematic search that identified 159 studies. Our findings highlight that this current research is highly contradictory, for example people with high trait neuroticism report excessive use despite appearing to use social media infrequently. We discuss the key trends across existing studies to date, and we consider the apparent difficulties experienced by people with high trait neuroticism in exploiting the full benefits of 'social' media, discussing the importance of considerations for both designers and users of social media platforms.